Calculating Some Topological Indices of SiO\(_2\) Layer Structure (Journal of Informatics and Mathematical Sciences, 2016)
Topological indices are closely related to the toxicological, physicochemical, pharmacological etc. properties of a chemical compound. This paper focuses on calculating topological indices namely RandiÄ‡ index, sum-connectivity index, reciprocal RandiÄ‡ index, reduced second Zagreb index and reduced reciprocal RandiÄ‡ index of SiO\(_2\) layer structure for all values of \(p\) and \(q\).
Keywords: Degree based indices; Topological indices; SiO\(_2\) layer structure